Performance of Sharia Cooperatives in Supporting Micro Business Development: Perspective of Sustainability and Financial Inclusion - Anisa Ayu Dwi Lestari (Sekolah Tinggi Agama Islam Kuningan, 2024)
Sharia cooperatives have an important role in expanding financial access and supporting the sustainability of micro-enterprises, especially in communities that prioritize sharia values. However, many micro-enterprises still have difficulty accessing conventional financing, thus hampering their development. This study aims to analyze the performance of sharia cooperatives in supporting the development of micro-enterprises through the perspective of sustainability and financial inclusion. The study used a quantitative method with a survey involving 200 sharia cooperatives as samples. The research instrument was a questionnaire with a Likert scale to measure various performance indicators of sharia cooperatives, sustainability of micro-enterprises, and financial inclusion. The results of the study showed that sharia cooperatives contributed significantly to the sustainability of micro-enterprises, especially through a more lenient profit-sharing financing system. In addition, sharia cooperatives are also able to increase financial inclusion in the unbanked community by providing flexible financial access. Regression analysis shows a positive relationship between the performance of sharia cooperatives and the sustainability of micro-enterprises and financial inclusion. In conclusion, sharia cooperatives not only provide financing but also support the empowerment of a more inclusive and sustainable micro-economy.